SOCIO-HYGIENIC IMPORTANCE OF TUBERCULOSIS OF ANIMALS - R. A. Nuratinov; N. Kh. Mesrobyan; E. A. Verdieva; A. A. Sultanov (Юг России: экология, развитие, 2014)
The survey of tuberculosis spreading in the world, Russia and Dagestan Republic, connected with peoples infection from sick animals, in given. Special attention is paid to the ways of infections transmission from animals to man